2015
DOI: 10.17305/bjbms.2015.242
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of ADH1B, ADH1C and ALDH2 in Turkish alcoholics: lack of association with alcoholism and alcoholic cirrhosis

Abstract: No data exists regarding the alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) gene polymorphisms in Turkish alcoholic cirrhotics. We studied the polymorphisms of ADH1B, ADH1C and ALDH2 genes in alcoholic cirrhotics and compared the results with non-cirrhotic alcoholics and healthy volunteers. Overall, 237 subjects were included for the study: 156 alcoholic patients (78 cirrhotics, 78 non-cirrhotic alcoholics) and 81 healthy volunteers. Three different single-nucleotide-polymorphism genotyping meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
7
0
3
Order By: Relevance
“…The frequency of the ALDH2 G/G genotype was higher than the ALDH2 G/A genotype in ALC patients 15 . Whereas, some studies have showed that there was no statistically significant relationship between the ALDH2 SNP rs671 polymorphism and ALC risk 16‐19 . According to the above studies, the results on the relationship between ALDH2 gene polymorphism and ALC are inconsistent.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The frequency of the ALDH2 G/G genotype was higher than the ALDH2 G/A genotype in ALC patients 15 . Whereas, some studies have showed that there was no statistically significant relationship between the ALDH2 SNP rs671 polymorphism and ALC risk 16‐19 . According to the above studies, the results on the relationship between ALDH2 gene polymorphism and ALC are inconsistent.…”
Section: Discussionmentioning
confidence: 95%
“… 9 , 13 , 14 , 15 Whereas, some studies have showed that there was no relationship between the ALDH2 polymorphism and ALC risk. 16 , 17 , 18 , 19 As for the studies on the relationship between ALDH2 gene polymorphisms and ALC, different sample sizes, inclusion criteria, regions, and ethnicities, as well as different standards of alcohol consumption, lead to different or even opposite results in such studies. 13 , 14 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…The metabolic rate can be influenced by genetic variants within a specific gene, for example; ADH (alcohol dehydrogenase) enzymes convert alcohol to acetaldehyde and acetaldehyde to acetate, which is influenced by functional polymorphisms within ADH1B, and this may increase the prevalence of alcoholic liver diseases [22]. In addition, many significant variants have been notified within the SLC19A1 gene from solute carrier family and were clinically functional including; rs1051266, rs12659 and rs1131596 [23].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are different international studies that correlate AUD with the occurrence of SNPs to ADH and ALDH genes; most of these studies were conducted in the Asian continent (Chiang et al, 2012;Lee, Chau, Yao, Wu, & Yin, 2006;Peng et al, 2002;Vatansever et al, 2015). In Brazil, however, there has been little research on this correlation.…”
Section: Introductionmentioning
confidence: 99%